Identification Of Selected Ageing-Related Proteins And The Characterisation Of Ptc4 In Yeast - Lee, Jee Whu (2022)
Ageing-related proteins play different roles in cellular processes such as regulating stress response, apoptosis, ubiquitin-proteasome system and signal transduction pathways amongst many others. Hundreds of ageing-related proteins have been revealed, but the roles of most of these ageing-related proteins are still unknown. In this study, the standardised chronological life span (CLS) assay, stress assay and growth assay were established. The CLS-extending effects of the ageing-related proteins, Ptc4, Zwf1, Sme1 and Sod1 selected from previous chronological life span (CLS) screen were validated through standardised colony forming unit (CFU) assay and the deletions of the selected ageing-related genes resulted in decreased CLS in yeast. Ptc4 contributes to oxidative stress tolerance in standardised oxidative stress assay and extends CLS the most among the selected ageing-related proteins. Zwf1 and Sod1 that contribute to oxidative stress tolerance in young cells, did not show oxidative stress tolerance in cells after prolonged ageing, suggesting the loss of oxidative stress tolerance capability after prolonged ageing. Besides, Ptc4 and Zwf1 promoted cell proliferation during cell growth upon protein overexpression in standardised growth assays, suggesting their involvement in cell division or growth pathways. Furthermore, loss of Ptc4 could still promote cell proliferation while loss of Zwf1 did not affect rate of cell proliferation. As Ptc4 could promote cell proliferation, the effects of other yeast type 2C protein phosphatases (PP2Cs) on rate of cell proliferation were also investigated in standardised growth assays.